Attribution of Criminal Responsibility Lessons from International Criminal Court and Tribunals - EBU, Alex Abang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This article explores the evolving concept of criminal responsibility within the context of international criminal law, drawing on lessons from the jurisprudence of the International Criminal Court (ICC) and various international tribunals. By examining the application of International Humanitarian Law (IHL) in non-international armed conflicts, particularly through the case of Libya, the article delves into how international law has progressively expanded its scope to hold non-state actors accountable for serious crimes. The discussion reflects on the transition of individual criminal responsibility from natural law principles, as reintroduced by the Nuremberg Trials, to its solidification as positive law under the Rome Statute. The article also addresses the gradual erosion of the non-intervention principle and the rise of international regulation over conduct traditionally managed by domestic law. It highlights how international criminal law navigates complex jurisdictional issues and contextual elements to impose liability, regardless of the perpetrator’s state affiliation, while recognizing the relevance of the actor’s status in determining crimes such as Crimes against Humanity or war crimes involving Prisoners of War. The dynamic and adaptable nature of international law is showcased in its ability to respond to global shifts and values.